Examining Green Banking Initiatives and Environmental Outcomes in Pakistan: The Role of Green Finance as a Moderator - Javeed Iqbal; Dr. Muhammad Gulzar; Laibah Hassan; Muhammad Islam (Indus Journal of Social Sciences, 2025)
This research emphasis to explore the green banking activities impacts on the commercial banks environmental performance and to identify the moderating effect of green finance sources to strengthening the relationship between Green Banking Activities like Green Banking marketing and Environmental Performance of Banks operating in Punjab province of Pakistan. Purposive sampling method is used to received response form the respondent. Structured Questionnaires are employed to collect primary data from the employees of the banks and 175 responses were recorded as sample size. Structural Equation Modelling was employed to examine the relationship among dependent, independent and moderator variable. The outcomes of this research discovered that GBA has a significant impact on BEP but the Sources of Green Finance (SGF) do not moderate the relationship between GBA and BEP. After that practical implications, limitation and future directions of this research are discussed.